Exploring green synthesis of parietin-mediated silver nanoparticles using γ-ray induced Xanthoria parietina foliose extracts for antibacterial potential - Sikander Ali; Alisha Moazzam; Saima Shahzad Mirza; Majid Mahmood; Sibtain Ahmed; Muhammad Usman Ahmad; Gildardo Rivera; Akhtar Rasool Asif; Muhammad Arshad; Mirza Imran Shahzad; Kaynat William; Sundas Sharif (Results in Chemistry)
In the current study, parietin was extracted aerobically from lichen and quantified using parietin activity tests. Different parameters were optimized to extract parietin, viz. suspending 1.5 g biomass of lichen in 15 mL methanol and incubating it for 45 min at 37 °C. Parietin-mediated AgNPs were synthesized by 30-minute procurement period with 3 mL of AgNO3 (3 mM) solution. Visual observations and ultraviolet–visible (UV–Vis) spectra demonstrated that the Ag precursor’s treatment changed the color of fresh methanolic extract to greenish-brown. Fourier transfer infrared (FTIR) spectroscopy was used to identify lichen secondary metabolites. The effective synthesis of Xa-AgNPs was further validated by X-ray diffraction patterns and scanning electron microscopy. The free parietin extract and synthesized nanoparticles (Xa-AgNPs) were evaluated for antimicrobial activity against selected bacterial isolates; S. aureus, B. subtilis (gram-positive), E. coli, Pseudomonas sp. (gram-negative) by agar well diffusion method. The results indicated that free parietin extract and synthesized nanoparticles (Xa-AgNPs) have potential antimicrobial activity against selected gram-positive and gram-negative bacterial isolates. The current results exhibited that Xa-AgNPs are potent bactericidal agents and should be considered a promising candidate to combat bacterial infections.